Proactive Solutions in Implementing Tribal Digital Sovereignty - Leeds, Stacy; Phillips, Samantha; Bledsoe Downes, Mikaela (The journal of community informatics, 2026)
This article argues that Tribal Nations must move rapidly from ad hoc digital practices to comprehensive legal and governance frameworks that fully implement Tribal Digital Sovereignty. Drawing on lessons from Indian gaming and other economic sectors, it shows how vendor-driven arrangements, weak contracts, and incomplete jurisdictional assertions have historically created long-term vulnerabilities around data, infrastructure, and regulatory authority. The article reframes digital systems—cloud services, health information technologies, broadband and spectrum, AI tools, and data-intensive enterprises—as core sites of sovereignty rather than as technical back-office functions. It contends that delays in regulating these domains allow external actors to harden jurisdictional and economic advantages that are difficult to unwind.To provide practical guidance, the article proposes four interlocking “buckets” of legal infrastructure: Tribal codes and regulations that assert digital jurisdiction; contracts and agreements that safeguard data ownership, limit sovereignty waivers, and require portability; easements and infrastructure arrangements that preserve Tribal authority over physical and virtual networks; and business registration systems that capture entities operating digitally in Tribal territories. It situates these tools within Indigenous Data Sovereignty frameworks such as the CARE Principles and emerging Tribal AI governance efforts, including early government policies that embed cultural values and guard against data exfiltration. The article further emphasizes workforce development, procurement strategies, and collaborative regional or inter-Tribal models as necessary conditions for sustained digital self-governance. Taken together, these approaches aim to ensure that Tribal sovereignty is exercised as powerfully in digital spaces as in the governance of land, resources, and institutions.